Influence of Need for Cognition and Need for Cognitive Closure on Information Behaviour - Fortier, Alexandre (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This project examines the influence of need for cognition and need for cognitive closure on information behaviour. Clear links between variations in the two variables observed in the literature and aspects of information behaviour are presented, along with a mixed methods design for the project. Ce projet examine l’influence du besoin cognitif et du besoin d’une finalité cognitive sur le comportement informationnel. Sont présentés des liens clairs entre les variations pour les deux variables observées dans la littérature et les aspects du comportement informationnel, ainsi que la conception de la méthodologie mixte du projet.